History and folklore of basmati rice - Ahuja, Subhash Chander; Ahuja, Uma; Ahuja, Siddharth (Journal of Cereal Research, 2019)
Basmati is an important food item as well as export commodity. Indian subcontinent has been bestowed by Mother Nature for this exclusive food and production area. Three colour variants have been known in Basmati as in many other rice varieties. Basmati surpasses all other scented varieties in shape, appearance, taste and quality. It has been the subject of debate and discussion in many seminars, symposia and adorned pages of books, magazines, websites and newspapers world over. In addition to its special cooking quality and medicinal value, it is a sought after donor in number of breeding programmes. So far, the earliest reported record of word Basmati is that of Heer Ranjha of Waris Shah (1766). This review presents additional records on word Basmati, historical area of cultivation, folk songs, folk tales, proverbs, associated with Basmati in states of Himachal Pradesh, Punjab, Uttarakhand, UP and Bihar. Basmati is not only an ambrosial food item but has been used to convey various aspects of life as a teaching medium, used as simile and as an adjective too. In addition it finds place in prayer offered to God. Of all the states, Uttarakhand seems to be proud and the richest source of Basmati folklore. This review on basis of large number of folkloric records corroborate with Dr. Khush’s postulation of Himalyan belt as Centre of diversity and spread of aromatic rices. DOI:https://doi.org/10.25174/2249-4065/2019/95207